Nonlinear soil-pile-structure interaction for midrise STMD buildings - Ghorbanzadeh, Mohammad; Uygar, Eris; Sensoy, Serhan (My University, 2021)
One of the effective vibration control systems used for structures is the semi active tuned mass damper (STMD), which is popular since it is reliable and simple. STMD characteristics in the design for piled foundations were usually obtained by modelling the foundation raft only to incorporate the soil structure interaction (SSI). However, as it proposed in the recent studies the role of SSI and simulation of piled raft in the analyses proved to be very important in the determination of the STMD parameters. Hence, in this study, efficiency of STMD with respect to the control of seismic response of the structure, was studied by considering the soil-pile-structure interaction (SPSI). Nonlinear time history analysis was applied for a three-layered soil profile including pile foundations by using the well-known substructure (spring) model under two different ground motion records. In order to increase the accuracy of the results, soil profile with piles and building structure with STMD were considered all at once in a single model under the action of seismic loading, named as direct method. P-Y curves which were suggested by American Petroleum Institute (API) were used in the spring method for simulating soil-pile-structure interaction. The results showed that, adjusting the STMD characterizations on piled structures without considering the soil-pile-structure interaction may result to ineffective control of the seismic vibration and in the worst case may lead to amplification of the vibration of buildings.
Keywords: İnşaat Mühendisliği; İnşaat ve Yapı Teknolojisi